City apartments - Koneman (Koln : Konemann, 2014)
House design is evolving fast following trends and the needs of our society. There is always a myriad of design schemes to meet diverse requirements; in other words, there is never a single solution to make the most of a living space. In the Essential Tips series, each book offers over 200 tips on different ways to create an environment that is functional and aesthetically pleasing. This book series explores contemporary design with exemplary case studies of homes with display innovative and practical design solutions.
Keywords: Apartments